Development of the Middle Layer in the Anther of Arabidopsis - Xue, Jing-Shi; Yao, Chi; Xu, Qin-Lin; Sui, Chang-Xu; Jia, Xin-Lei; Hu, Wen-Jing; Lv, Yong-Lin; Feng, Yi-Feng; Peng, Yu-Jia; Shen, Shi-Yi; Yang, Nai-Ying; Lou, Yu-Xia; et al. (Frontiers in Plant Science, 2021)
The middle layer is an essential cell layer of anther wall located between endothecium and tapetum in Arabidopsis. Based on sectioning, the middle layer was observed to be degraded at stage 7 which lead to the separation of tapetum from anther wall. Here, we established techniques for the living image of the anther. We created several marker lines with fluorescence proteins expressed in all anther layers to study the anther development. Several staining methods were used in the intact anthers to study anther cell morphology. We clarified the initiation, development, and degradation of the middle layer in Arabidopsis. It is initialed from both the inner and outer secondary parietal cells at stage 4, stopped cell division at stage 6, and finally degraded at stage 11. Its neighbor cell layers, the epidermis, and endothecium continued cell division until stage 10, which leads to a thin middle layer. The degradation of the tapetum cell wall at stage 7 leads to its isolation from the anther wall. This work presents the fundamental knowledge of the middle layer development which facilitates the further investigation of anther development and plant fertility. These living image methods could be useful in future studies.